Gestión financiera y su incidencia en la rentabilidad de la empresa comercial “Torito” durante el año 2022”. - Palma Nájera , Carlos Enrique (2024)
The purpose of this research is to reveal how inadequate financial management affects the profitability of the commercial company Torito. This research aims to evaluate financial management and its impact on profitability to obtain a real perspective of the company's financial situation. Financial management is a process that is responsible for combining the fulfillment of established objectives and goals with financial planning and financial analysis in order to together be able to apply optimal measures that help the company have adequate financial management. Currently, in the local environment there is a frequent problem where many commercial companies and ventures have serious profitability problems, due to inadequate financial management, which can lead to the closure of these businesses. This research is qualitative, quantitative, descriptive and analytical. In which methods such as inductive, deductive, historical logical analysis, observation and data collection were used. And the use of instruments such as interviews and surveys. Given the results obtained, we can observe the dynamics of the transactional activities of the commercial company which have a positive effect on financial management. It is worth mentioning that the profitability indicators were favorable; however, it is recommended that the company invest in training for its workers and thus improve their processes and it was also identified that tools and linked information systems are used which streamline processes and decision making.